2011
DOI: 10.1248/bpb.34.1413
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions of Postweaning Protein Malnutrition in Mice

Abstract: An inadequate supply of nutrition is one of the main nongenetic factors affecting brain development.1) Liu et al. 2) demonstrated that children with malnutrition signs at three years of age tend to have low IQ, excessive motor activity and antisocial behavior in adulthood. In the framework of such nutritional inadequacy, early protein malnutrition (PM) adversely affects central nervous system (CNS) maturation, resulting in long-lasting, or even permanent, deleterious effects. 3,4)Malnutrition is a common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…This data may reflect differences in the plasticity between the developing and mature mouse brain. It is also consistent with our previous report on the induction in mice of behavioral effects such as alterations in cognitive function 21) and reduced anxiety behavior 41) by PM during the prepubertal but not postpubertal stage. Recently it has become apparent that brain development continues through adolescence and that prepubescence represents a period sensitive to nutritional deficits, 42) drug abuse 43) and isolation rearing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This data may reflect differences in the plasticity between the developing and mature mouse brain. It is also consistent with our previous report on the induction in mice of behavioral effects such as alterations in cognitive function 21) and reduced anxiety behavior 41) by PM during the prepubertal but not postpubertal stage. Recently it has become apparent that brain development continues through adolescence and that prepubescence represents a period sensitive to nutritional deficits, 42) drug abuse 43) and isolation rearing.…”
Section: Discussionsupporting
confidence: 93%
“…41) There are indications that hippocampal 5-HT 1A receptors are crucial for the modulation of these behaviors. 57,58) Indeed, it has been demonstrated that hippocampal 5-HT 1A receptor activation produces anxiolytic-like effects.…”
Section: Discussionmentioning
confidence: 99%
“…One possible underlying mechanism of the negative relationship of underweight and overweight/obesity to academic performance is associated with worsened executive function 7,8,[14][15][16] , which is closely related to academic performance 12,25 . However, we could not elucidate the underlying mechanisms of the negative relationship of childhood underweight and overweight/obesity to the academic performance from the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Kar et al 14 showed that children with malnutrition demonstrated poor cognitive task performance requiring executive function. In an animal study, malnutrition intervention reduced brain weight associated with poor executive function in mice 16 . Although the mechanisms may be different, both overweight/obesity and underweight could impair executive function and, in turn, cause poor academic performance.…”
Section: Introductionmentioning
confidence: 97%
“…Overall, the additive effect of hypoxia and rotation on body weight may be explained by 1) a decreased nutritional output to the pups due to rotation, 2) stress induced by changes in feeding behavior and/or metabolism and 3) changes in maternal care due to stressful effects of rotation on the mother, none of which are mutually exclusive and may all contribute partially or completely to decreased pup body weight. Certainly, handling, removing dams from pups (albeit typically for extended periods of time), changes in nutrition and maternal care, have all been shown to individually and collectively influence pup growth and brain development [4, 6, 8, 11, 15, 28, 32, 36, 42]. However, the relative contribution of these factors to changes observed in body and brain weight remains to be determined.…”
Section: Discussionmentioning
confidence: 99%